A history of violence - Cronenberg, David, 1943-; Mortensen, Viggo, 1958-; Bello, Maria, 1967-; Harris, Ed, 1950-; Hurt, William; Holmes, Ashton; Suschitzky, Peter; Shore, Howard; Wagner, John, 1949-; Locke, Vince; New Line Home Entertainment (Firm); Warner Home Video (Firm) (Burbank, CA : New Line Home Entertainment : Distributed by Warner Home Video, 2006)
Tom is a loving, well-respected family man from a small Indiana town. When two criminals show up at his diner, Tom is forced to take action and thwart the robbery attempt. Suddenly heralded as a local hero who took the courage to stand up to crime, people look up to Tom as a man of high moral regard. But all the media attention attracts the likes of the mob, who show up at Tom's doorstep.
Title from container.
Based on the graphic novel by John Wagner and Vince Locke.
Originally released as a motion picture in 2005.
Director of photography, Peter Suschitzky ; art director, James McAteer ; editor, Ronald Sanders ; music, Howard Shore ; costume designer, Denise Cronenberg ; production designer, Carol Spier.
Viggo Mortensen, Maria Bello, Ed Harris, William Hurt, Ashton Holmes, Peter MacNeill, Stephen McHattie, Greg Bryk.
MPAA rating: R; for strong brutal violence, graphic sexuality, nudity, language and some drug use.
Keywords: Mistaken identity -- Indiana -- Drama; Heroes -- Indiana -- Drama; Restaurateurs -- Indiana -- Drama; Feature films; Thrillers (Motion pictures, television, etc.); Films for the hearing impaired; Thriller -- Feature; Crime -- Feature